Prestimulus α/β power in temporal-order judgments: individuals differ in direction of modulation but show consistency over auditory and visual tasks - Boenke, Lars T.; Zeghbib, Abdelhafid; Spiliopoulou, Myra; Alais, David; Ohl, Frank W. (Frontiers in Computational Neuroscience, 2023)
In a spatial temporal-order judgment (TOJ) task, we presented auditory and visual stimulus pairs in randomly interleaved order while recording EEG. This allowed us to test spontaneous shifts of prestimulus oscillatory activity in each modality without employing a cue or task switch. For veridical and nonveridical TOJs, the power spectral density (PSD) was calculated for 3 frequencies (5 Hz steps: 10, 15, and 20 Hz). We found on the group level: 1) Veridical auditory TOJs, relative to nonveridical, were associated with higher β-band (20 Hz) power over central electrodes. 2) Veridical visual TOJs showed higher α-band (10, 15 Hz) power over parieto-occipital electrodes 3) Electrode site interacted with TOJ condition in the α-band: For auditory TOJs, PSD over central electrodes was higher for veridical than nonveridical and over parieto-occipital electrodes was lower for veridical than nonveridical trials, while the latter pattern was reversed for visual TOJs. While our group-level result showed a clear direction of prestimulus modulation, the individual-level modulation pattern was variable and included activations opposite to the group mean. Interestingly, our results at the individual-level mirror the situation in the literature, where reports of group-level prestimulus modulation were found in either direction. Because the direction of individual activation of electrodes over auditory brain regions and parieto-occipital electrodes was always negatively correlated in the respective TOJ conditions, this activation opposite to the group mean cannot be easily dismissed as noise. The consistency of the individual-level data cautions against premature generalization of group-effects and suggests different strategies that participants initially adopted and then consistently followed. We discuss our results in light of probabilistic information processing and complex system properties, and suggest that a general description of brain activity must account for variability in modulation directions at both the group and individual levels.